Pengaruh Good Governance Dan Kompetensi Sumber Daya Manusia Terhadap Kinerja Pegawai (Studi pada Dinas Pariwisata Kabupaten Ciamis) - Dian Sundari; Enas Enas; Aan Anwar Sihabudin (Jurnal Bintang Manajemen, 2023)
Information technology is not followed by an increase in knowledge, skills and work attitudes of employees in carrying out their duties and responsibilities. In addition, employee performance is affected by good governance which is not optimal due to the absence of transparent data in improving staff quality and lack of employee involvement in the decision-making process and the competence of human resources is not optimal because there are still many employees who do not have a high level of education and the rapid development of information technology is not followed by an increase in knowledge, skills and work attitudes of employees in carrying out their duties and responsibilities. The research was conducted using a quantitative explanatory survey method. The data analysis technique used is descriptive statistics, inferential statistical analysis with multiple regression models. The results of the study inform (1) Good governance has a positive and significant effect on employee performance at the Ciamis District Tourism Office. This means that the better the good governance, the higher the performance of employees at the Ciamis Regency Tourism Office. (2) Competence has a positive and significant effect on employee performance at the Ciamis Regency Tourism Office. This means that the higher the competency, the higher the employee performance at the Ciamis Regency Tourism Office. (3) Good governance and competence have a positive and significant effect on employee performance at the Ciamis District Tourism Office. This means that the better the good governance and competence, the higher the employee performance at the Ciamis Regency Tourism Office.